Garlic, from Remedy to Stimulant: Evaluation of Antifungal Potential Reveals Diversity in Phytoalexin Allicin Content among Garlic Cultivars; Allicin Containing Aqueous Garlic Extracts Trigger Antioxidants in Cucumber - Hayat, Sikandar; Cheng, Zhihui; Ahmad, Husain; Ali, Muhammad; Chen, Xuejin; Wang, Mengyi (Frontiers in Plant Science, 2016)
Garlic has the charisma of a potent remedy and holds its repute of a therapeutic panacea since the dawn of civilization. An integrated approach was adopted to evaluate the genetic diversity among Chinese garlic cultivars for their antifungal potency as well as allicin content distribution and, furthermore; a bioassay was performed to study the bio-stimulation mechanism of aqueous garlic extracts (AGE) in the growth and physiology of cucumber (Cucumis sativus). Initially, 28 garlic cultivars were evaluated against four kinds of phytopathogenic fungi; Fusarium oxysporum, Botrytis cinerea, Verticillium dahliae and Phytopthora capsici, respectively. A capricious antifungal potential among the selected garlic cultivars was observed. HPLC fingerprinting and quantification confirmed diversity in allicin abundance among the selected cultivars. Cultivar G025, G064 and G074 had the highest allicin content of 3.98, 3.7 and 3.66 mg g-1 respectively, whereas G110 was found to have lowest allicin content of 0.66 mg g-1. Cluster analysis revealed three groups on the basis of antifungal activity and allicin content among the garlic cultivars. Cultivar G025, G2011-4 and G110 were further evaluated to authenticate the findings through different solvents and shelf life duration and G025 had the strongest antifungal activity in all conditions. Leaf disc bioassay against Phytophthora capsici and Verticillium dahliae to comparatively study direct action of AGE and Allicin aqueous standard (AAS) during infection process employing eggplant and pepper leaves showed a significant reduction in infection percentage. To study the bioactivity of AGE, a bioassay was performed using cucumber seedlings and results revealed that AGE is biologically active inside cucumber seedlings and alters the defense mechanism of the plant probably activating ROS at mild concentrations. However, at higher concentrations, it might cause lipid peroxidation and membrane damage which temper the growth of cucumber seedlings. At the outcome of the study, an argument is advanced that current research findings provide bases for cultivar selection in antifungal effectivity as well as genetic variability of the cultivars. Allicin containing AGE can be used in specialized horticultural situations such as plastic tunnel and organic farming as a bio-stimulant to enhance cucumber growth and attenuate fungal degradation of agricultural produce.